2019
DOI: 10.1007/s10494-019-00013-3
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of High-Fidelity Simulations for Main Gas Path Turbomachinery Components and Their Industrial Impact

Abstract: Over the past two decades high-fidelity simulations have become feasible for most main gas path turbomachinery components. This paper introduces the key challenges of simulating and modelling turbomachinery flows and presents an overview of possible simulation strategies. A comprehensive overview is given of which particular design challenges have to date been addressed by high-fidelity simulations, with a particular focus on high-pressure and centrifugal compressors, and high-pressure and low-pressure turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 178 publications
(234 reference statements)
0
19
0
Order By: Relevance
“…In the present study, we investigate the bypass transition in an HPT working at conditions representative of a modern aircraft engine (Sandberg & Michelassi 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we investigate the bypass transition in an HPT working at conditions representative of a modern aircraft engine (Sandberg & Michelassi 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous simulations had very limited spanwise extent, and thus the length scales of the inlet turbulence were too small to represent realistic conditions. In the present study, we investigate the bypass transition in an HPT working under conditions representative of a modern aircraft engine (Sandberg & Michelassi 2019). By performing highly resolved simulations with up to 8.6 × 10 8 grid points, the flow physics can be investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…High fidelity simulations, including Direct Numerical Simulation (DNS) and Large-Eddy Simulation (LES), have been shown to be very accurate in simulating turbomachinery flows [4]. By resolving most of the energy-containing turbulent scales in the unsteady flow field in an HPT, LES are able to provide insight into complex flow physics including the impact of curvature and pressure gradient on boundary layers, and the two-way interaction between incoming turbulence and boundary layer transition [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Lower levels of turbulence modelling are obtained for LES approach compared to RANS [38,39] that may expect a better resolution of the flow field at the interface between cavity and main annulus flow. From a loss perspective, recent studies have shown that the assessment of loss in a gas turbine can be obtained more accurately by LES compared to RANS [18,20] , this being due to a better resolution of turbulent field that drives the mixing process of momentum and enthalpy which in turns controls the level of losses generated in the flow field [35] . This paper uses the exergy formalism to draw the loss generated in a low-speed linear cascade with an upstream cavity including a parametric study of the purge flow rate supplied to the cavity and the rim seal geometry.…”
Section: Introductionmentioning
confidence: 99%